Captação de águas pluviais na cidade de Campina Grande – PB: Alternativa para uma política de enfrentamento da escassez de água nas escolas públicas - Silva, Ozéas Jordão da (2003)
This is work present the proposal that the pluvial water catchment in the Campina Grande’s public schools is an politics for confrontation of the problem of water scarcity in the city. Stating fron the discussion on the phenomenon of the drought in the region of the Brazilian Semi-arid, this work concentrates its focus on the specific problem of Campina Grande’s analyzing 39 of its schools. The result of research show: that the schools make exclusive use of system of supply of state Company – CACEPA – and that her terms infrastructures conditions are precarious, especialy, in the periods water rationing in the city; that the steps by the directors of the schools in the attempt to fight the serious damages of the complex system educational caused by water scarcity are inefficient; that the schools buildings roofs posse such of the a great capacity of rain water catchment that by adopting the system of rain water catchment out of the schools, 15 would be super-suficients, 15 almost-coefficients and 9 insufficient, with respect to relation of water catchment versus water demand, that the student community knows buildings. Hence, it is concluded, that the system of pluvial water catchment present a helpful, viable, efficient and economic alternative for combating the scarcity in the Campina Grande’s public schools.